2009
DOI: 10.1002/cctc.200900129
|View full text |Cite
|
Sign up to set email alerts
|

Selective Catalytic Hydrogenation of Functionalized Nitroarenes: An Update

Abstract: Scheme 1. Hydrogenation of a herbicide intermediate: Successful catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
400
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 628 publications
(415 citation statements)
references
References 65 publications
5
400
0
4
Order By: Relevance
“…Moreover, catalytic nitroarene hydrogenation has typically involved batch liquid phase systems operated at elevated pressures. 42,[77][78][79][80] The use of b-Mo 2 N to promote ultra-selective continuous gas phase (atmospheric pressure) hydrogenation represents a new direction in the production of industrially important aromatic amines. It must be noted that the b-Mo 2 N catalytic system has not been optimized and future work will consider the role of the nitride crystallographic phase/surface area and the catalytic consequences of combining a transition metal (e.g.…”
Section: Gas Phase Hydrogenation Of P-chloronitrobenzene (P-cnb)mentioning
confidence: 99%
“…Moreover, catalytic nitroarene hydrogenation has typically involved batch liquid phase systems operated at elevated pressures. 42,[77][78][79][80] The use of b-Mo 2 N to promote ultra-selective continuous gas phase (atmospheric pressure) hydrogenation represents a new direction in the production of industrially important aromatic amines. It must be noted that the b-Mo 2 N catalytic system has not been optimized and future work will consider the role of the nitride crystallographic phase/surface area and the catalytic consequences of combining a transition metal (e.g.…”
Section: Gas Phase Hydrogenation Of P-chloronitrobenzene (P-cnb)mentioning
confidence: 99%
“…[19] Oxidation of the pinacolate ligand by the molybdenum(VI) center gives rise to the oxomolybdenum(IV) species, MoOCl 2 (dmf) 2 (Me 2 CO) (B), [20] bearing a weakly coordinated molecule of acetone that is immediately displaced by the sulfoxide in solution to give the unstable MoOCl 2 (dmf) 2 (R 1 SOR 2 ) adduct (C), which in turn regenerates the catalyst releasing the sulfide. To support our proposal, we treated our catalyst, MoO 2 Cl 2 (dmf) 2 , with pinacol in a molar ratio 1:1.2 in MeCN and, while unable to fully characterize any oxomolybdenum(IV) species, we could isolate in high yield the dinuclear oxomolybdenum(V) complex Mo 2 O 3 Cl 4 (dmf) 4 , [21] which displayed similar catalytic activity to that of MoO 2 Cl 2 (dmf) 2 . [22] This result could be explained as it is known that oxomolybdenum(IV) complexes, formed via oxoabstraction, present a strong tendency to comproportionate with the parent dioxomolybdenum(VI) species, and that this process is only inhibited by the presence of bulky ligands that prevent the formation of the dinuclear species.…”
mentioning
confidence: 95%
“…Due to the high potential of sulfoxides as intermediates in a variety of synthetic transformations, mainly as chiral auxiliaries, there is a continuous interest in the development of novel methods for their deoxygenation to the corresponding sulfides, [2] as this is usually the first step for their further removal. Moreover, the selective reduction of aromatic nitro compounds, [3] that encompass hydrogenation, [4] electron-transfer [5] and hydride-transfer [6] reactions, is the principal method for accessing anilines. Among all of these strategies, the catalytic hydrogenation has experienced a significant development.…”
mentioning
confidence: 99%
“…Bao et al reported that Ag/SiO2 with Ag nanoparticle size of 7-9 nm catalyzed the selective hydrogenation of chloronitrobenzenes to their corresponding chloroanilines 29) . Selective hydrogenation of nitro group in the presence of other reducible functional groups (such as olefinic groups) is an important reaction to produce functionalized anilines as industrial intermediates for a variety of specific and fine chemicals 101) . Stoichiometric amount of reducing agents such as iron, sodium hydrosulfite, tin, or zinc in ammonium hydroxide have been used to reduce aromatic nitro compounds containing olefinic bonds.…”
mentioning
confidence: 99%